Pendampingan Penggunaan Media Ajar Adaptif untuk Siswa Berkebutuhan Khusus di SD Inklusi - Endang Sri Maruti; Vivi Rulviana; Tiara Intan Cahyaningtyas; Fida Rahmantika Hadi; Rischa Pramudya Trisnani; Novita Erliana Sari; Rizka Rahmawati; Wemphi Novan Ramadhan; Dita Meilia; Cindi Fatika Amelia; Inin Ananta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Inclusive education aims to ensure that all students, including those with special needs, receive an adequate education. Adaptive educational media has become an increasingly important tool for facilitating learning for students with special needs in inclusive schools. This program aims to help inclusion teachers develop and implement adapted teaching materials for students with special needs in inclusive primary schools in Magetan Regency. This program explores the concept of mentoring, the benefits of adaptive media, and how mentoring can enhance the effectiveness of using adaptive media to support the learning of students with special needs. The implementation approach begins with a reinforcement and socialization phase, continues with a mentoring implementation phase, and ends with an evaluation phase. In the context of inclusive education, the use of adaptive instructional materials, accompanied by thoughtful support, can help students with special needs realize their learning potential. Adaptive educational media enables personalized learning, while advisors provide the guidance and support students need. The combination of these two factors plays an important role in supporting successful inclusive education.